Urgensi Sanad dalam Meningkatkan Profesionalitas Guru Pendidikan Agama Islam - Muhammad Hamid; Syamsul Bakri (PT. Pusmedia Group Indonesia, 2023)
As technology develops, Islamic Religious Education teachers are challenged to further develop their intellectual abilities so they don't lose their role to digital technology. One of the best and most appropriate methods for Islamic Religious Education teachers to increase knowledge is to study with teachers who are at a higher level or more experienced than them or are known as a sanad ‘ilm in Islam. The purpose of this research is to explain its importance a sanad ‘ilm as one of the aspects that a teacher must have in order to become a professional teacher in his field. This study uses a literature approach (Library Research) and descriptive analysis in writing so that the results of this study are in the form of an explanation of the collected library data. The results of this study explain that the method takes a sanad ‘ilm with the aim of increasing aspects of a teacher's knowledge is very important and has the basis of the arguments of the Qur’an and Hadith. It doesn't end there, even with a sanad ‘ilm the scientific knowledge of a teacher will at least get three benefits, namely can improve intellectual aspects, scientific originality, objective in viewing, and principled in science. Keywords: Urgency of Sanad; Intellectual Ability; PAI Teachers Professionalism.